Efficacy and Safety of Aspirin for Primary Cardiovascular Risk Prevention in Younger and Older Age: An Updated Systematic Review and Meta-analysis of 173,810 Subjects from 21 Randomized Studies - Calderone, Dario; Greco, Antonio; Ingala, Salvatore; Agnello, Federica; Franchina, Gabriele; Scalia, Lorenzo; Buccheri, Sergio; Capodanno, Davide (Thrombosis and Haemostasis, 2021)
Aims The efficacy and safety of aspirin for primary cardiovascular disease (CVD) prevention is controversial. The aim of this study was to investigate the efficacy and safety of aspirin in subjects with no overt CVD, with a focus on age as a treatment modifier.Methods and Results Randomized trials comparing aspirin use versus no aspirin use or placebo were included. The primary efficacy outcome was all-cause death. The primary safety outcome was major bleeding. Secondary ischemic and bleeding outcomes were explored. Subgroup analyses were conducted to investigate the consistency of the effect sizes in studies including younger and older individuals, using a cut-off of 65 years. A total of 21 randomized trials including 173,810 individuals at a mean follow-up of 5.3 years were included. Compared with control, aspirin did not reduce significantly the risk of all-cause death (risk ratio: 0.96; 95% confidence interval: 0.92–1.00, p = 0.057). Major adverse cardiovascular events were significantly reduced by 11%, paralleled by significant reductions in myocardial infarction and transient ischemic attack. Major bleeding, intracranial hemorrhage, and gastrointestinal bleeding were significantly increased by aspirin. There was a significant age interaction for death (p for interaction = 0.007), with aspirin showing a statistically significant 7% relative benefit on all-cause death in studies including younger patients.Conclusion The use of aspirin in subjects with no overt CVD was associated with a neutral effect on all-cause death and a modest lower risk of major cardiovascular events at the price of an increased risk in major bleeding. The benefit of aspirin might be more pronounced in younger individuals.
Keywords: aspirin; primary prevention; meta-analysis